Muknalia is a Collared Peccary (Pecari tajacu): A Reply to Stinnesbeck et al. (22nd June 2021) - Schubert, Blaine W.; Samuels, Joshua X.; Chatters, James C.; Arroyo-Cabrales, Joaquin
Several years ago, a new genus and species of peccary, " Muknalia minima ", was described from the Pleistocene of Mexico. We previously examined that specimen and concluded that it was synonymous with the extant collared peccary, Pecari tajacu, but that taxonomic revision is rejected by the authors of the original study (this volume). Here, we provide further analysis of " Muknalia " and expand on previous evidence from both morphology and taphonomy that support synonymy with P. tajacu . We argue that morphological features, both in terms of size and shape, that were used to diagnose " Muknalia " all fall within the range of variation of the extant P. tajacu, or are a consequence of taphonomic modification, including human handling.